EFEK PENDAPATAN SEBAGAI MODERASI FAKTOR YANG MEMPENGARUHI PERILAKU MANAJEMEN KEUANGAN - asfia, aenul; Supramono, Supramono; Lestari, Rohmini Indah (Kinerja, 2023)
This research was conducted to examine the effect of financial literacy, locus of control and financial attitudes on financial management behavior with income as a moderator. The purpose of this study was to analyze the effect of financial literacy, locus of control and financial attitudes on financial management behavior with income as moderating which has the characteristics of the Millennial Generation. The criteria for the sample taken in this study were the Millennial Generation or the generation born in 1980–1995 or ages ranging from 27–42 years with a total of 160 respondents. The analysis technique of this research uses SmartPLS (Partial Least Square). The results of the study show that the relationship between financial literacy, locus of control, financial attitudes and income has a positive and significant influence on financial management behavior. Meanwhile, financial literacy, locus of control and financial attitudes when moderated by income have no effect on financial management behavior.